Durabilitas Campuran Aspal Emulsi Dingin dengan Substitusi Serbuk Karet Ban Bekas sebagai Agregat Halus - Karyawan, I Dewa Made Alit; Mahendra, Made; Sideman, Ida Ayu Oka Suwati; Yuniarti, Ratna; Fajrin, Jauhar (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The increasing number of motor vehicles in Indonesia has led to a rise in waste tires, which are difficult to decompose naturally. Utilizing this waste as road construction material aligns with the principles of reduce, reuse, and recycle. This study aims to analyze the effect of waste tire crumb rubber as a fine aggregate substitute on the Marshall characteristics and volumetric parameters of Cold Asphalt Emulsion Mixture (CAEM). The experimental method was conducted using five substitution levels (0%, 5%, 10%, 15%, and 20%), which were tested using the Marshall Test to determine stability, flow, Marshall Quotient (MQ), and volumetric parameters (VIM, VMA, VFA). The addition of recycled rubber from waste tires influences the mechanistic behavior of asphalt mixtures. Test results show a trend of increasing VIM and decreasing VMA and VFA, with the optimal void balance achieved at a rubber content of 5–10%. The elastomeric properties of the rubber particles enhance the elastic deformation capacity, thereby improving the mixture’s flexibility up to a 5% content. At 10%, the flow value decreases, indicating greater stiffness or stability. Higher contents tend to disrupt the continuity of the asphalt matrix and weaken the aggregate bonding, consistent with the material’s viscoelastic behavior. Therefore, a 5% rubber content provides the best balance between stability, flexibility, and void characteristics, while also improving the durability of the asphalt mixture. The use of this material offers environmental benefits by reducing solid waste and supporting the concept of sustainable development in pavement construction. Further studies are recommended to include water susceptibility tests, evaluations of plastic deformation under repeated loading, and field-scale testing to verify performance under actual service conditions